EXPERIMENTAL INVESTIGATION OF A SOLAR COOKER USING COLLECTOR WITH HEAT PIPES - Esen, Mehmet; Hazar, Hanbey; Esen, Hikmet (Yildiz Technical Univ, 2005)
In this study, a solar cooker coupled vacuum-tube collector with integrated heat pipes was constructed and tested experimentally. The heat pipes made of copper were filled with a refrigerant as the heat transfer fluid of the solar collector. The refrigerant studied were Freon 404A and Freon 410A. The experiments were performed on several clear days in Elazig, and the experimental results recorded on days having similar meteorological conditions were presented here to evaluate the performance of the cooker. The solar radiation, ambient temperature, and temperatures at various points of the cooker system were measured. The different foods were cooked with the cooker in 25-73 min periods.
Keywords: Solar cooker; Vacuum-tube collector; Heat pipe; Refrigerant